Dipeptidyl peptidase IV (DPP-IV/CD26) inhibitory and free radical scavenging potential of W. somnifera and T. foenum-graecum extract - Anand Krishna Singh; Jaya Joshi; Rameshwar Jatwa (International Journal of Phytomedicine, 2013)
The incretin hormone glucagon-like peptide 1 (GLP-1), proposed as a new target for the treatment of type 2 diabetes, is rapidly cleaved by dipeptidyl peptidase-IV enzyme (DPP-IV/CD26). DPP-IV inhibitors enhance circulating GLP-1 level, which in turn resulted into improved glucose tolerance and insulin secretion. The present study was designed to evaluate DPP-IV inhibitory activities vis a vis anti-peroxidative potential, if any, in two antidiabetic plants. We studied in vitro DPP-IV inhibition; DPPH radical scavenging potential; ß-carotene bleaching; reducing power and total phenolics content at the varying concentrations (0.1 – 1 mg/ml) in the extracts of W. somnifera (WS) root and T. foenum-graecum (TFG) seeds. Methanolic extract (0.5 mg/ml) of WS inhibited DPP-IV activities (69.7 ±0.56%) at greater extent than that of TFG (51.8±1.24%), as compared to control. WS extract contains relatively higher amount of total phenolics, elevated DPPH free radical scavenging potential and pronounced reducing power efficacy than that of TFG. The result of present study ravel that WS and TFG extracts contain some novel DPP-IV inhibitors with antiperoxidative potential and could be developed as therapeutic molecules for type 2 diabetes mellitus.